Impactof menopausal symptoms on quality of life (QOL) within six months of systemic breast cancer treatment: Results from the Shanghai Breast Cancer Survival Study (SBCSS) - Dorjgochoo, Tsogzolmaa (2009)
Menopausal symptoms (MPS) after breast cancer treatment are associated with reduced health-related quality of life (QOL) among Caucasian women. Little is known about whether MPS similarly impact QOL in Asian women with breast cancer. QOL was assessed by using the Generic Quality of Life Inventory (MOSQOL-74) or Short Form-36 Health Survey (SF-36) in 4,976 Chinese participants of the Shanghai Breast Cancer Survival Study who were treated for incident, non-metastatic breast cancer within the six months before the study interview. Relationships between MPS and QOL were assessed by multiple linear regression, controlling for potential confounders. 71.4% of study participants experienced MPS, including hot flashes, night sweats, vaginal dryness, depressed mood, and/or dry skin. Women with MPS reported lower overall QOL than women without MPS [mean scores 61.0 vs. 64.0, respectively (MOSQOL-74) and 54.9 vs. 66.9, respectively (SF-36); P<0.01]. Adjusted mean differences (β) in overall QOL in the presence and absence of MPS were −3.1 (95% CI -3.8, −2.4) with the MOSQOL-74 and −12.3 (95% CI -13.8, −10.9) with the SF-36. Women with any MPS had lower scores for the MOSQOL-74 physical and psychological domains and for the SF-36 social and emotional subscales than those without MPS (P<0.05 for all). Having a higher number of MPS predicted poorer QOL in all domains measured regardless instrument used (P(trend)<0.01 for all). Our study indicates that in Chinese women with recently-treated breast cancer, MPS adversely impacts QOL. Actively soliciting and treating MPS in these women should significantly improve their QOL.